2009
DOI: 10.1007/s11031-009-9150-4
|View full text |Cite
|
Sign up to set email alerts
|

Achievement incentives determine the effects of achievement-motive incongruence on flow experience

Abstract: Previous research has shown that incongruence between implicit and explicit achievement motives impairs flow experience. We examined this relationship in a more differentiated manner by arguing that achievement-motive incongruence only exerts negative effects when individuals act in situations in which achievement incentives are present and arouse conflict between the two motives. In nonachievement situations, no negative effects of achievementmotive incongruence on flow experience are expected. Study 1 and St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 41 publications
2
40
0
2
Order By: Relevance
“…This might be the reason for the inconsistent results reported in terms of the convergent and discriminant validity of the MMG. Regarding discriminant validity, some authors have not found significant correlations between MMG and selfreport measures (Langens and Schmalt 2008;Schüler 2010;Schüler et al 2008;Sokolowski et al 2000), whereas for example Kehr (2004) reported a significant correlation between MMG achievement and PRF achievement. Regarding convergent validity, as already mentioned above, the achievement motive score of a precursor of the MMG was significantly correlated with the achievement motive score of the TAT (Schmalt 1999), whereas other researchers have failed to replicate this association for the MMG (Brunstein and Heckhausen 2008).…”
Section: Moderation Analysesmentioning
confidence: 98%
“…This might be the reason for the inconsistent results reported in terms of the convergent and discriminant validity of the MMG. Regarding discriminant validity, some authors have not found significant correlations between MMG and selfreport measures (Langens and Schmalt 2008;Schüler 2010;Schüler et al 2008;Sokolowski et al 2000), whereas for example Kehr (2004) reported a significant correlation between MMG achievement and PRF achievement. Regarding convergent validity, as already mentioned above, the achievement motive score of a precursor of the MMG was significantly correlated with the achievement motive score of the TAT (Schmalt 1999), whereas other researchers have failed to replicate this association for the MMG (Brunstein and Heckhausen 2008).…”
Section: Moderation Analysesmentioning
confidence: 98%
“…For example, in some studies no significant correlations with explicit motive measures were found (e.g., Schmalt and Langens 1996;Schüler 2010;Schüler et al 2008) but in other studies a moderate degree of convergence with explicit motive measures was revealed (e.g., Kehr 2004). Furthermore, as far as the authors know, studies demonstrating that motive arousal (through an experimental manipulation) leads to corresponding changes in MMG scores (sensitivity to motive-arousal) are missing so far.…”
Section: The Multi-motive Gridmentioning
confidence: 99%
“…Because the subscales achievement, affiliation, and dominance fit the theoretical conceptualization of the achievement, affiliation, and power motive very well, the scales have often been used as explicit motive measures (Brunstein and Maier 2005;Kehr 2004;Schüler 2010). Besides the English original version (Jackson 1984), a German version of the PRF (Stumpf et al 1985) also exists.…”
Section: Personality Research Form (Prf)mentioning
confidence: 99%
“…According to Csikszentmihalyi (1990), flow experience is closely associated with positive emotions, a high level of concentration, intrinsic motivation and the sense of control. Schüler (2010) stated that individuals experience intrinsic motivation in activities that are within their interests; they entirely focus on these types of activities. The autotelic experience, which Csikszentmihalyi (1997) has described as intrinsic motivation, is a significant feature of flow experience.…”
Section: Flow Theorymentioning
confidence: 99%
“…By accumulating activities that are appropriate for the purpose of their life, they both achieve their personal development and reach happiness with a sense of control over the activity, which occur in their consciousness. The relevant literature shows that flow theory is used in diverse disciplines, such as positive psychology (Park & Peterson, 2009), sport psychology (Jackson & Ecklund, 2002), educational psychology (Rathunde & Csikszentmihalyi, 2005), organizational psychology (Nielsen & Cleal, 2010), organizational effectiveness (Hoefer, 2008), technology addiction (Cooper, 2009), motivation (Havitz, 2005;Schüler, 2010), job performance (Fullagar & Kelloway, 2009), distance education (Belchior, 2007) and marriage (DuPree, 2007), with various variables examined.…”
Section: Flow Theorymentioning
confidence: 99%